The persistence of the block as an urban structure: a comparative study of the typology of the Berlin Block - Nottingham, Megan U. (2019)
This dissertation proposes a comparative study of the Berlin block, the city’s ubiquitous typology of the late nineteenth century and the form of the 1970s block. The study seeks to examine the block’s historical transformation based on the historical and typological interpretation. It sheds light on the specific moment in architectural history, in which the form was reinstated in Berlin’s urban fabric. After several decades of extensive criticism of the block since the form’s inception, the typology returned and proliferated in Berlin at the time of the Internationale Bauaustellung 1979-1984/87, known as Berlin International Building Exhibition, the IBA. This new planning framework, embraced the formal qualities of the nineteenth century’s block in a modified form: its density, dynamic mix of uses and programmes, together with a vibrant street life and spatiality defining urban space. These values were sought in the regeneration of the existing urban fabric as well as in new developments; they were further adopted in the new planning strategy - the 1995 Planwerk Innenstadt, and are said to be yet again reevaluated for the ‘vision and inspiration’ by the future planning framework, Stadtenwicklungskoncept, 2030 (the Urban Development Concept, Berlin 2030) (Bodenschatz, 2010, Bradley and Hedrén, 2014, Senate Department for Urban Development and Environment, 2013).